Effects of strength, explosive and plyometric training on energy cost of running in ultra-endurance athletes - Giovanelli, N.; Taboga, P.; Rejc, E.; Lazzer, S. (European Journal of Sport Science, 2017)
The aim of the present study was to evaluate the effects of a 12-week home-based strength, explosive and plyometric (SEP) training on the cost of running (Cr) in well-trained ultra-marathoners and to assess the main mechanical parameters affecting changes in Cr. Twenty-five male runners (38.2 ± 7.1 years; body mass index: 23.0 ± 1.1 kg·m-2; VO2max: 55.4 ± 4.0 mlO2·kg-1·min-1) were divided into an exercise (EG = 13) and control group (CG = 12). Before and after a 12-week SEP training, Cr, spring-mass model parameters at four speeds (8, 10, 12, 14 km·h-1) were calculated and maximal muscle power (MMP) of the lower limbs was measured. In EG, Cr decreased significantly (p < .05) at all tested running speeds (-6.4 ± 6.5% at 8 km·h-1; -3.5 ± 5.3% at 10 km·h-1; -4.0 ± 5.5% at 12 km·h-1; -3.2 ± 4.5% at 14 km·h-1), contact time (tc) increased at 8, 10 and 12 km·h-1 by mean +4.4 ± 0.1% and ta decreased by -25.6 ± 0.1% at 8 km·h-1 (p < .05). Further, inverse relationships between changes in Cr and MMP at 10 (p = .013; r = -0.67) and 12 km·h-1 (p < .001; r = -0.86) were shown. Conversely, no differences were detected in the CG in any of the studied parameters. Thus, 12-week SEP training programme lower the Cr in well-trained ultra-marathoners at submaximal speeds. Increased tc and an inverse relationship between changes in Cr and changes in MMP could be in part explain the decreased Cr. Thus, adding at least three sessions per week of SEP exercises in the normal endurance-training programme may decrease the Cr.